1996
DOI: 10.7164/antibiotics.49.815
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cholesteryl Ester Transfer Protein by Rosenonolactone Derivatives.

Abstract: Several recent clinical trials have demonstrated that lower plasma cholesterol levels do indeed have a beneficial effect on events related to coronary heart diseases. (Fig. 1) were isolated from the culture of fungus strain F1064, that was isolated from a soil sample collected at Mt. Jiree, Kyun-815 gnamProvince, Korea. It was taxonomically identified as Trichothecium roseum by the method of Pitt and Hocking.9) A 2-ml portion of the seed culture was inoculated into a 1-liter baffled flask with four baffles co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…2 This structure possesses quaternary centres at C-4, C-9, C-10 and C-13 and consequently it is difficult using conventional chemical means, to functionalise rings A and C. A number of rosanes are biologically active and recently as a result of screening studies, it was concluded that rosenonolactone analogues may be good models for the design of new inhibitors of the cholesteryl ester transfer protein. 3 It was therefore of interest to examine the use of microbiological transformation in order to introduce hydroxyl groups into rings A and C.The fungus, Mucor plumbeus, has been used for the biotransformation of terpenoids. Incubation of rosenonolactone 1 with M.plumbeus for seven days on shake culture gave five metabolites which were separated by chromatography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 This structure possesses quaternary centres at C-4, C-9, C-10 and C-13 and consequently it is difficult using conventional chemical means, to functionalise rings A and C. A number of rosanes are biologically active and recently as a result of screening studies, it was concluded that rosenonolactone analogues may be good models for the design of new inhibitors of the cholesteryl ester transfer protein. 3 It was therefore of interest to examine the use of microbiological transformation in order to introduce hydroxyl groups into rings A and C.The fungus, Mucor plumbeus, has been used for the biotransformation of terpenoids. Incubation of rosenonolactone 1 with M.plumbeus for seven days on shake culture gave five metabolites which were separated by chromatography.…”
mentioning
confidence: 99%
“…6β-Hydroxyrosenonolactone 2: m.p.185-187°C (lit., 4 180-181°C), (Found:M + 332.197 Calc. for C 20 H 28 0 4 M + 332.199), υ max /cm -l 3431, 1763, 1713, 1637; δH 0.97 (3H,s,H-17), 1.11(3H,s, H-20), 1.40(3H,s,H-18), 2.60(1H,dd, J 4.1 and 11.8 Hz, H-8), 2.88(1H,br.s.OH) (disappears on treatment with 2 H 2 0),3.96(1H,dd, J 1.9 and 4.9 Hz, H-6) (collapses to doublet J 4.9 Hz, on treatment with 2 H 2 0), 4.92 (lH,dd, J 10.7 and 0.9 Hz), 5.00 (lH,dd, J 17.5 and 0.9 Hz) (each H-16), 5.82 (lH,dd, J 10.7 and 17.5 Hz, H-15).15,16-Epoxyrosenonolactone 3: m.p, 168-172°C, (Found: M + 332.197 C 20 H 28 0 4 requires 332.199), υ max /cm -1 1756, 1714; δ H 0.86(3H,s, H-17), 0.92(3H,s, H-20), 1,11(3H,s, H-18), 2.62 (2H,d, J 3.2 Hz, H-16), 2.75(1H,t, J 3.2 Hz, H-15). 12α-Hydroxyrosenonolactone 4: m.p.…”
mentioning
confidence: 99%
“…Support for this idea was recently obtained in a rabbit atherosclerosis model using a CETP inhibitor (). Several CETP inhibitors have been described, including monoclonal antibodies (), apolipoproteins ( , ), amphipathic peptides ( 5 , , amphipathic small molecules such as cholesteryl sulfate and lipopolysaccharide that modify lipoprotein structure ( , ), as well as various small molecules including sterols, polycyclic natural products and heterocyles ( ). Some compounds have been shown to irreversibly inactivate CETP following cysteine modification, suggesting that a cysteine residue may reside in or near the neutral lipid binding site ( 12 , 13 , 20−22 , 35 ).…”
mentioning
confidence: 99%
“…This investigation led to the isolation and identification of one new cleistanthane-type diterpene named engleromycenolic acid A ( 1 ), one new rosane-type diterpene named engleromycenolic acid B ( 2 ) and one new natural rosane-type diterpene named engleromycenol ( 3 ), along with three known rosane-type diterpenes: rosololactone ( 4 ), rosenonolactone ( 5 ) and 7-deoxyrosenonolactone ( 6 ) [7]. Their structures (Fig.…”
Section: Introductionmentioning
confidence: 99%